Knowledge and attitudes of nurses regarding patient rights: a Corum/Turkey sample - Akca,Selen Ozakar (2015)
Summary Objective: patient rights are defined as the rules of conduct between the people who benefit from health services and the health institutions and personnel who provide them. As the protection and provision of these rights are closely related to the nursing trade, these professionals must have thorough knowledge about this issue. The purpose of this study was to evaluate the acquaintance and attitudes of working nurses in Corum/Turkey regarding patient rights and to create the basis for a planned educational program. Methods: sample selection was not performed in this study, but all nurses (n=939) who were working in the course of this study constituted the sample. Survey forms were used as data collection tools. Results: the study revealed that 92.3% had received education about patient rights, 2.2% had never heard anything about this term and 86.6% became aware of it through sources from outside of school. It was established that the attitudes of nurses regarding patient rights differ for every patient and that this rate ranges from 35.8 to 98.1%. Conclusion: there is a requirement for more studies on the subject of patient rights, as they play an important role in the development of health services. In that regard, patient rights centers should be established and carried out according to the foreseen model set by national and international health systems. Studies aiming to teach health personnel, patients and their relatives about patient rights must be carried out.